Conversational Documentarianism in Instagram - Bañuelos, Jacob (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2015)
What are the semiotic characteristics of Instagram interface and how it contributes to the construction of documentary photographic conversational speech for social purposes? The semiotic analysis of conversational interface for Instagram as interactive platform for creating new strategies for documentary photography for social purposes, was made using the model proposed by Bettetini text conversation (1984) and from the multidimensional concept of interactivity proposed by Sally McMillan (2006). Thus, the work of Pachi Tamer (cachafaz) on Instagram and specifically the case "Jim - Oktoberfest" is analyzed, the site One-dollar-dreams and the case of "Sebastian" by the same author, from a semiotic perspective.